Value of Prostate-Specific Antigen and Prostate-Specific Antigen Density in Detection of Prostate Cancer in an Iranian Population of Men - Ghafoori, Mahyar; Varedi, Peyman; Hosseini, Seyed Jalil; Asgari, Mojgan; Shakiba, Madjid (Urology Journal, 2009)
Introduction: The objective of this study was to evaluate the value of serum prostate-specific antigen (PSA) and prostate-specific antigen density (PSAD) in the diagnosis of prostate cancer. Materials and Methods: A total of 330 consecutive patients suspected of having prostate cancer due to either abnormal digital rectal examination or elevated serum PSA levels underwent transrectal ultrasonography-guided sextant biopsy of the prostate. The PSA and PSAD values were assessed based on the biopsy results. Results: One hundred and twenty-one patients (36.7%) had prostate cancer. In this group, the mean PSA was 31.60 ± 30.85 ng/mL (range, 1.9 ng/mL to 166.0 ng/mL) and the mean PSAD was 0.83 ± 1.01 (range, 0.04 ng/mL/cm3 to 6.38 ng/mL/cm3). In those without prostate cancer the mean PSA and PSAD levels were 13.80 ± 18.72 ng/mL (range, 0.4 ng/mL to 130.0 ng/mL; P < .001) and 0.24 ± 0.32 (range of 0.01 ng/mL/cm3 to 2.29 ng/mL/cm3; P < .001). The receiver operating characteristic curve analysis revealed that the discriminating power of serum PSA for detecting prostate cancer, as estimated by the area under the curve, was 0.74 while that for PSAD was 0.81 (P < .001). For the PSA range of 3.5 ng/mL to 41 ng/mL (gray zone) the areas under the curve was 0.68 for PSA, while it was 0.78 for PSAD (P < .001). Conclusion: The use of PSAD instead of PSA in the diagnosis of prostatic cancer improves the diagnostic accuracy.